Islamic Education Teachers’ Strategies in Instilling Character Education at MTs Al-Ahsan Bogor - Nuraini, Nuraini; Subagiya, Bahrum; Basri, Samsul (Journal of Educational Management and Strategy, 2025)
The rapid development of digital technology has significantly influenced the lives of young people, particularly Generation Z. Social media, as part of the digital lifestyle, brings both positive and negative impacts on the character formation of students. This study aims to explain the strategies implemented by Islamic Education teachers in instilling the values of faith (aqidah), morality (akhlaq), and proper etiquette (adab) among Generation Z students at MTs Al-Ahsan Bogor. The background of this research lies in the increasing negative influence of social media, which potentially threatens the character and spirituality of adolescents. This research employs a descriptive qualitative approach with data collection methods consisting of observation, interviews, and documentation. The findings reveal that Islamic Education teachers at MTs Al-Ahsan apply the strategy of internalizing faith values through role modeling in attitude and behavior, as well as habituation of adab through practical implementation within the school environment. Furthermore, parental involvement and collaboration with the school play a significant role in supporting students’ character development. The consistent and gradual integration of Islamic values has shaped students’ personalities to become morally upright, strong in faith, and ethically responsible in using social media. These findings demonstrate that character education based on Islamic values is both relevant and effective in protecting the younger generation from the harmful effects of the digital world.